Ethical Problems Created by the Cultural Differences Between Migrants and the Native Population of Receiving Cities. (2nd September 2020) - Garcia-Zamor, Jean-Claude
Abstract : The article shows that multiculturalism can be an opportunity for host cities to develop a more open-minded, tolerant, and diverse culture and a more ethical society. The cultural differences between migrants and the native population of receiving cities often raise various ethical dilemmas because these differences in culture and their connected virtues can be perceived as insurmountable. Utilitarianism has been adopted as the ethical theoretical framework through which the article has been developed. It provides a coherent ethical perspective for the discussion of the topic. When identifying economic impacts, such as those of housing; healthcare; education; and population density, utilitarianism connects these problems to underlying ethical dimensions. The article draws out the policy implications of the analysis and findings. Immigration is currently one of the most debated public policies both in the United States and in Europe and will remain so for many years. It is safe to predict that it will continue to be the subject of future scholarly research.